Productivity in private and public food industries of Iran - Afrooz, Ahmad; Abdul Rahim, Khalid (Marsland Press, 2011)
One of Iran’s most important industries is food industries that has a large effect on Iranian economy. The number of public food industries has decreased from 246 units in 1995 to 127 units in 2006. On the other hand the number of private food industries has increased from 1636 units in 1995 to 2077 units in 2006. Due to these changes in ownership this paper examined the labor productivity and total productivity in private and public food industries of Iran in 1995-2006 period. The results show that, unlike the normal theory where the private sector is always better, labor productivity and total factor productivity in public sectors of food industries were higher than private sectors industries over the period. The main responses for this inconsistency are due to higher wages, higher capital per worker and lower women employees in public sector against private sectors of food industries.